Chondroitin polymerizing factor promotes breast carcinoma cell proliferation, invasion and migration and affects expression of epithelial‐mesenchymal transition‐related markers. Issue 2 (7th January 2021) - Li, Yang; Gong, Hui; Feng, Lei; Mao, Dan; Xiao, Yujie; Wang, Yunqi; Huang, Lizhong
Abstract : Chondroitin polymerizing factor (CHPF) plays an important role in the development of certain malignant tumors. However, the role of CHPF in breast carcinoma (BRCA) and its underlying mechanism are still not fully elucidated. Expression profiles for CHPF in BRCA tissues were retrieved from The Cancer Genome Atlas database and used for prognostic analysis. Cell viability, invasion and migration were measured in vitro using MCF7 and MDA‐MB‐231 cell lines upon knockdown or over‐expression of CHPF. Bioinformatic analysis showed that CHPF was substantially upregulated in BRCA tissues, and a quantitative reverse transcriptase‐PCR was performed to confirm its upregulation in BRCA cells. High expression of CHPF was observed to be significantly associated with pathologic stage, metastasis and worse prognosis. We also observed that depletion of CHPF significantly inhibited cell proliferative, invasive and migratory abilities, whereas overexpression of CHPF exerted the opposite effects. Furthermore, analysis of the GEPIA database revealed that CHPF expression is positively correlated with the epithelial–mesenchymal transition‐related markers vimentin, Snail, Slug and motion‐related protein matrix metallopeptidase 2; these findings were confirmed via western blotting. Our data suggest that CHPF may contribute to BRCA progression by modulating epithelial–mesenchymal transition‐related markers and matrix metallopeptidase 2 expression. Abstract : Here, we found that chondroitin polymerizing factor is upregulated in breast carcinoma and associated with worse prognosis according to bioinformatic analysis. Functionally, chondroitin polymerizing factor acts as an oncogene that promotes breast carcinoma cell progression by facilitating proliferation, invasion and migration, as well as by elevating the expression of matrix metallopeptidase 2 and epithelial–mesenchymal transition‐related markers.